Empowerment communication in an Islamic boarding school as a medium of harmonization - Sulaiman, Adhi Iman; Ahmadi, Dadi (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study aims to analyze empowerment communication in a cooperative of an Islamic boarding school as a medium of harmonization. The study used a qualitative research method for Participatory Learning and Action (PLA). Data were collected through interviews, documentation, observation, and Focus Group Discussion (FGD). Informants were selected purposively and snowball sampling, namely the organization committee and students at the Islamic Boarding School, the management of cooperatives, business groups in the community, and village government, as well as practitioners, and activists of community empowerment. The study location was determined in community and Al Muaddib Islamic boarding school at Cilacap district, Central Java Province of Indonesia. The study used data analysis of community development, namely identifying, categorizing problems, specific objectives, analyzing problems and preparing action plans, evaluating the entire process, and action plans. The results of research i.e. (1) The empowerment communication should be developed to perform a comprehensive economic empowerment program ranging from the identification of the problem, the potential of human resources, natural resources and the economy of rural communities up to the analytical solution of cooperative programs, assistance and partnerships to realize harmonization. (2) Empowerment communication should be carried out sustainably and comprehensively with a humanistic, dialogical, egalitarian and participatory approach starting from counselling to provide motivation, inspiration, knowledge, and then improving skills with training, monitoring, evaluation and partnership. (3) The study implication is that empowerment communication programs could be a medium for harmonization, eliminating traumatic and negative stigma against society and Islamic boarding school which are considered radical.